EVALUATION OF CIAWI RESERVOIR EFFECTIVENESS IN CILIWUNG WATERSHED, BOGOR, JAWA BARAT AS A FLOOD CONTROL EQUIPMENT OF DKI JAKARTA - Fachri Maulvi, Muhammad
Ciawi reservoir is located in Cipayung Village, Megamendung District, Cisarua, Bogor Regency, West Java Province with an area of catchment 87,9 km2. The Ciawi reservoir is planned with the type of dry dam or with the aim of a flood control reservoir, where the Ciawi Reservoir is one of the integrated development projects in reducing flood disasters in the downstream area of the Ciliwung-Cisadane River, namely DKI Jakarta. The maximum reservoir volume is 6.562.082 m3, the normal condition volume is 4.249.213 m3, with sedimentation volume is 215.092 m3, and the effective reservoir volume is 6.346.990 m3. The effectiveness value is calculated by comparing the reduction discharge with the inflow discharge. The effectiveness value of Ciawi Reservoir flood reduction with Q50 is 49,2% with ?Tp for 3 hours, the effectiveness of Q100 is 38,9% with ?Tp for 3 hours, and the effectiveness of Q1000 is 19,8% with ?Tp for 2 hours. The overflow building is planned with side overflow and ogee type of crest (USBR) with a PMF flood discharge 2247,57 m3/s, and a total length of overflow building is 403 m. Design rainfall is analyzed using the Gumbel Distribution Method. The flood discharge hydrograph of the plan is calculated using ITB-2 Method. Sedimentation rates were calculated using the USLE, SDR, and Brune Trap Efficiency Methods. The planned budget and cost for the overflow building is Rp. 123.313.934.642,39.